2012
DOI: 10.1002/jsfa.5957
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of protein hydrolysates from whole anchovy sprat (Clupeonella engrauliformis) prepared using endogenous enzymes and commercial proteases

Abstract: Anchovy sprat hydrolysates showed high antioxidant activities and amino acid contents and low heavy metal concentrations, indicating that they have high potential for use in human and animal diets. The high antioxidant activities are related to the high levels of hydrophobic amino acids found in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 34 publications
4
40
1
Order By: Relevance
“…The values of DH in may be useful in preparing hydrolysates with certain functional properties, since the DH is the principle determinant of protein hydrolysate properties. The result was in accordance to [28] in which DH of yellow tuna fish increased with increase in hydrolysis time.…”
Section: Dhsupporting
confidence: 86%
See 2 more Smart Citations
“…The values of DH in may be useful in preparing hydrolysates with certain functional properties, since the DH is the principle determinant of protein hydrolysate properties. The result was in accordance to [28] in which DH of yellow tuna fish increased with increase in hydrolysis time.…”
Section: Dhsupporting
confidence: 86%
“…For instance, the concentration of protein at pH 4 is 60.68±0.3 µg/µl at 60 minutes, whereas at 90 minutes, it increases to 63.60±0.9 µg/µl. In hydrolysates high protein recovery ranged from 63% to 71% and has been increased with increasing incubation time, similar trend was also reported by Nemati et al [25], Ovissipour et al [28]. It is due to the ionic strength or hydrophobicity and also indicates that maximum peptide bonds are broken, and free amino acids are released.…”
Section: Protein Recoverysupporting
confidence: 83%
See 1 more Smart Citation
“…The hydrolysates from neutrase and alcalase had the lowest DH among the six hydrolysates, these being 15.71±0.016 and 16.05±0.014 %, respectively. Ovissipour et al (2013) reported the DH of hydrolyzed proteins from a whole anchovy sprat (Clupeonella engrauliformis) with alcalase, flavourzyme, papain and bromelain. Those were 55.8±0.56, 30.5±2.1, 49.74± 2.6 and 43.05±2.7 %, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Alemán et al (2011a, b) determined the antioxidant activity of squid and tuna skin hydrolysates and found that the ABTS activity decreased in the case of alcalase, collagenase, trypsin and pepsin hydrolysates of both squid and tuna. Ovissipour et al (2013) reported that the whole anchovy sprat protein hydrolysate with alcalase had the greatest ABTS activity, while flavourzyme showed the lowest activity among all hydrolysates. This difference may arise from the different DH of alcalase in each study and from the different starting materials.…”
Section: Antioxidant Activities Of Each Hydrolysatementioning
confidence: 99%